2023
DOI: 10.3390/antiox12020298
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lactic Acid Bacteria Fermentation on Phenolic Compounds and Antioxidant Activity of Avocado Leaf Extracts

Abstract: The growing global consumption of avocados, associated with contents including bioactive compounds with numerous health-promoting properties, is producing a large amount of agro wastes around the world. Different management approaches are available for the recovery of bioactive compounds from wastes as potential ingredients for use in the production of functional foods and nutraceuticals. Lactic acid fermentation can be used to exploit nutritional potential and add value to agro wastes. In this study, fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 59 publications
2
32
1
Order By: Relevance
“…The fermentation of avocado seeds by LAB could lead to several benefits, such as improving their bioactivities, a field of research that has not been deeply studied. In avocado leaves, the fermentation by LAB has led to satisfactory results [13]. Recently, Rozan et al reported a reduction in the anti-nutrients tannins, oxalates, and alkaloids contents of 80.76%, 89.95%, and 70%, respectively, by fermenting avocado seed with LAB [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fermentation of avocado seeds by LAB could lead to several benefits, such as improving their bioactivities, a field of research that has not been deeply studied. In avocado leaves, the fermentation by LAB has led to satisfactory results [13]. Recently, Rozan et al reported a reduction in the anti-nutrients tannins, oxalates, and alkaloids contents of 80.76%, 89.95%, and 70%, respectively, by fermenting avocado seed with LAB [14].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above and the results obtained in previous research [13], this study aimed to evaluate the effect of submerged fermentation with different LAB on the polar profile of avocado seeds, evaluating the antioxidant and the antidiabetic activities, in comparison to an unfermented avocado seed extract.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of a circular economy and considering the number of bioactive compounds present in the avocado leaves, it could be of great interest to use the avocado leaf wastes as a raw material to high-value food products. Recently, De Montijo-Prieto et al (2023) proposed the use of avocado leaf waste for the extraction of bioactive compounds; anyway, their use as raw material for high-value food products could be more environmentally sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, De Montijo‐Prieto et al . (2023) proposed the use of avocado leaf waste for the extraction of bioactive compounds; anyway, their use as raw material for high‐value food products could be more environmentally sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…The fermented kimchi is known for a high levels of lactic acid bacteria, has investigated the many health beneficial effects such as antioxidant, anticancer, and antiobesity [14]. A study has also reported that the fermentation of avocado leaves by lactic acid bacteria exhibited higher antioxidant activities [15]. Therefore, many studies focus on the immune improving effects of natural products to develop functional materials from food sources using lactic acid bacteria fermentation.…”
Section: Introductionmentioning
confidence: 99%